Gestão de portifólio de projetos: uma análise do processo de seleção de projetos de esporte de alto rendimento - Santos, Catarina Duarte dos (2014)
This study addressed the management of portfolio of projects focused on the selection of projects of high performance sport (EAR) in private sports organizations process. This was a qualitative exploratory research using a single case study. The unit of analysis in question was selected due to the interest shown in research by top management, availability of data collection, the structure of the sports programs and the results presented by teams of RAS in the national and international scene. To structure this research, in search of knowledge and clarification of the selection processes used for EAR projects, we generated the following research question: how is the process of selecting projects for high performance sport (RAS) in organizations private sports? Selected for this study models were models of portfolio selection Ghasemzadeh & Archer (1999) and stage-gate Cooper, Edgett, & Kleinschmidt (2001) with the aim of analyzing the practices suggested in the literature for selecting portfolio projects, and Spliss (De Bosscher et al., 2009) model that addresses pillars that contribute to sports performance, with the objective of verifying the unit of analysis as the EAR projects are aligned with the pillars that make up the model. We analyzed the process of selection of projects in the EAR unit of analysis based on variables determined in accordance with the theoretical framework and the end of the study it was possible to analyze how the process of selection of projects in the EAR unit of analysis and suggest important for structuring a process of selection of projects EAR efficient for private sports organizations points. It was found that the results contributed to the elaboration of a list of suggestions for structuring a process of selection of sports projects in various sports events (participation, education and competition), demonstrating the applicability in other types of organizations.